MASA KECIL YANG DIRAMPAS: ANALISIS EKSPLOITASI EKONOMI DAN PELANGGARAN HAK ANAK PADA KASUS ANAK YANG DIPAKSA MENJADI JURU PARKIR DI LAMPUNG - Ririn Arliza Sidauruk; Eldika Simanjuntak; Seistha Herdianna; Alesandro Garcia; Johanes Melvin Takarianto; Chontina Siahaan (CV. Denasya Smart Publisher, 2026)
Child economic exploitation remains a serious issue in Indonesia and constitutes a violation of children's fundamental rights. This study aims to analyze the forms of economic exploitation and violations of children's rights in the case of RA, an 11-year-old child in Bandar Lampung who was forced by her mother to work as a parking attendant and submit a daily target of IDR 200,000 while experiencing physical violence for approximately two years. This research employed a qualitative method with a case study approach using secondary data obtained from scientific literature, laws and regulations, and media reports. Data were analyzed descriptively through the perspectives of the Theory of Children's Rights, the Theory of Child Economic Exploitation, and the Theory of Child Protection. The findings reveal that the case represents a systematic violation of children's rights, including the right to protection from exploitation, the right to education, the right to play, and the right to optimal growth and development. The study also finds that the exploitation experienced by RA was not merely an economic issue but reflected broader structural failures within the child protection system involving the family, community, and law enforcement institutions. The case demonstrates that existing child protection mechanisms tend to be reactive rather than preventive. Therefore, stronger collaboration among families, communities, and government institutions is necessary to prevent child exploitation and ensure the fulfillment of children's rights.